The compound (E)-2-(3,4-dihydroxystyryl)-3-hydroxy-4H-pyran-4-one alleviates neuroinflammation and cognitive impairment in a mouse model of Alzheimer’s disease - Xueyan Liu; Wei Wu; Xuejuan Li; Chengyan Wang; Ke Chai; Fanru Yuan; Huijuan Zheng; Yuxing Yao; Chenlu Li; Zu-Cheng Ye; Daijun Zha (Neural Regeneration Research)
Previous studies have shown that the compound (E)-2-(3,4-dihydroxystyryl)-3-hydroxy-4H-pyran-4-one (D30), a pyromeconic acid derivative, possesses antioxidant and anti-inflammatory properties, inhibits amyloid-β aggregation, and alleviates scopolamine-induced cognitive impairment, similar to the phase III clinical drug resveratrol. In this study, we established a mouse model of Alzheimer’s disease via intracerebroventricular injection of fibrillar amyloid-β to investigate the effect of D30 on fibrillar amyloid-β–induced neuropathology. Our results showed that D30 alleviated fibrillar amyloid-β–induced cognitive impairment, promoted fibrillar amyloid-β clearance from the hippocampus and cortex, suppressed oxidative stress, and inhibited activation of microglia and astrocytes. D30 also reversed the fibrillar amyloid-β–induced loss of dendritic spines and synaptic protein expression. Notably, we demonstrated that exogenous fibrillar amyloid-β introduced by intracerebroventricular injection greatly increased galectin-3 expression levels in the brain, and this increase was blocked by D30. Considering the role of D30 in clearing amyloid-β, inhibiting neuroinflammation, protecting synapses, and improving cognition, this study highlights the potential of galectin-3 as a promising treatment target for patients with Alzheimer’s disease.